Dinamika Ekonomi Politik Media Digital: Analisis Berbasis Teori Kritis tentang Kasus Kontemporer di Indonesia - Suharto Suharto; Raden Panji Supriyadi; Udi Rusadi; Syafrul Syafrul; Sahrul Ramadhan (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The development of digital technology has driven structural changes in the media system, information production patterns, and the relationship between media, the state, and society. The author presents a descriptive-narrative analysis of the dynamics of the political economy of digital media by utilizing several critical theories: the political economy of media (Mosco, McChesney, Dwyer), the cultural industry (Adorno & Horkheimer), hegemony (Gramsci), framing (Entman), the propaganda model (Herman & Chomsky), and digital capitalism (Fuchs, Srnicek, Zuboff). This study also combines a literary approach with empirical examples in Indonesia, including the phenomenon of buzzers, political influencers, digital polarization, and the role of platforms such as TikTok, YouTube, Instagram, and WhatsApp in shaping public opinion. The findings show that the media structure in Indonesia is now hybrid, combining conventional media ownership oligarchy and global platform oligopoly, and creating a fragmented public sphere. This research emphasizes the need for a new theoretical model capable of explaining the interaction of the state, capital, and platforms within the framework of digital capitalism.